Reversing Desertification - In Practice - Savory, Allan (Annals of Arid Zone, 2016)
Electric lights were not, nor could they have been, developed by the finest candle makers. Einstein reputedly said we were unlikely to solve our problems with the same thinking that produced them. History is replete with examples of significant new thinking and problem solving arising from people in unrelated fields. Such people were not blinded by the paradigms of expertise in the area of concern. [n this paper [, with a background in botany and zoology, and a wildlifer by passion, describe simply why past civilizations throughout the world failed due to the symptoms of biodiversity loss or desertification. I add field experience and logic to Smut's theory of Holism. This is combined with almost fifty years of trial and error field work in many countries, backed by research in fields seemingly unrelated to desertification. The outcome is the discovery of an unsuspected cause of desertification that explains why, despite the best efforts of range managers in many nations, deserts continue to advance. The work led to the development of a holistic framework for decision-making and policy formation, that is proving encouragingly successful through empowering people to reverse land degradation, biodiversity loss and its many symptoms wherever applied.